Принципы модернизации системы циркуляции хладоагента в локальной ВЧ гипертермии - Поспелов, Л. А.; Колесник, Константин Васильевич (НТУ "ХПИ", 2014)
В работе проведен анализ трёх принципиально различных систем циркуляции хладагента (СЦХ), предназначенных для обеспечения одной и той же задачи: охлаждения поверхности тела пациента в момент проведения лечебной гипертермической процедуры. Рассмотрены системы - фреоновая, криогенная и выполненная на основе использования элементов Пельтье. Выявлены сравнительные достоинства и недостатки каждой из них в указанном применении и предложен наиболее оптимальный вариант в виде комбинации двух последних. Проанализированы достоинства и недостатки одного из наиболее оптимальных его технических решений.

The analysis of three fundamentally different coolant circulation systems (CCS), designed to provide the same problem: the patient's body surface cooling at the time of therapeutic hyperthermia treatments. Particle systems - freon, cryogenic and executed based on the use of Peltier elements. Revealed comparative advantages and disadvantages of each of them in this application and offered the best option as a combination of the last two. The advantages and disadvantages of one of its most optimal technical solutions. It is shown that any of the "System refrigerant" alone is not able to fully meet the "Medical and technical requirements" imposed on therapeutic hyperthermia complex "Ekstraterm -XXI". The possibility of using Peltier elements as complementary staff "System refrigerant" to dampen fluctuations in temperature on the electrodes - applicators. Established the relevance of research problems ripple "System refrigerant" adjustable temperature for the formulation of the requirements for the Peltier module.
Principles of the modernization of the local circulation cooling RF hyperthermia
Keywords: онкология; фреон; криоагент; элемент Пельтье; болюс; алгоритм; oncology; hyperthermia; refrigerant; freon; cryoagent; Peltier element; bolus algorithm